The investigation of antimicrobial activity of some s-substituted bis-1,2,4-triazole-3-thiones - Karpun, Ye.; Parchenko, V.; Fotina, T.; Demianenko, D.; Fotin, A.; Nahornyi, V. V.; Nahorna, N.; Карпун, Євген Олександрович; Парченко, Володимир Володимирович; Нагорний, Володимир Володимирович; Нагорна, Наталія Олександрівна (My University, 2021)
New S-substituted 4-alkyl-5-((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl)thio)methyl)-4H-1,2,4-triazole-3-thiol derivatives have been designed, synthesized and studied their antimicrobial activity on 11 standard Gram-positive and Gram-negative microorganism strains. Their spectral and physicochemical parameters were established using modern comprehensive methods of analysis, including 1H NMR spectroscopy, GC-MS and elemental analysis.It has been found that compound 2a exhibits strong suppression of 5 test strains (MBC = 15.6 μg/mL). Compound 4a showed moderate inhibition of Salmonella pullorum, Escherichia coli O2, Salmonella enteritidis strains (MBC = 31.25 μg/mL) Compound 6a was sensitive toward ten tested bacteria at 31.25 μg/mL concentration.
Keywords: 1,2,4-triazole; organic synthesis; antimicrobial activity